2007
DOI: 10.1111/j.1365-313x.2007.03171.x
|View full text |Cite
|
Sign up to set email alerts
|

Semagenesis and the parasitic angiosperm Striga asiatica

Abstract: SummaryOver the last several years, intermediates in the reduction of dioxygen have been attributed diverse functional roles ranging from protection against pathogen attack to the regulation of cellular development. Evidence now suggests that parasitic angiosperms, which naturally commit to virulence through the growth of new organs, depend on reduced oxygen intermediates, or reactive oxygen species (ROS), for signal generation. Clearly, the role of ROS in both plant defense and other physiological responses c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 44 publications
0
50
1
Order By: Relevance
“…Haustorium development was significantly reduced in transgenic roots silenced for QR1, but not QR2 transcripts. Transgenic roots for pHpQR1 had about a 10-fold reduction in QR1 transcripts compared with nontransgenic roots, and these roots developed haustoria about 3 to 4 (A) The lignin component (i) is oxidatively decarboxylated to DMBQ (ii) through the actions of fungal peroxidases, host peroxidases, or mild abrasion (Caldwell and Steelink, 1969;Keyes et al, 2007). (B) DMBQ (ii) and peonidin (iii) enter the parasite cells, possibly by nonselective diffusion (Shann and Blum, 1987).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Haustorium development was significantly reduced in transgenic roots silenced for QR1, but not QR2 transcripts. Transgenic roots for pHpQR1 had about a 10-fold reduction in QR1 transcripts compared with nontransgenic roots, and these roots developed haustoria about 3 to 4 (A) The lignin component (i) is oxidatively decarboxylated to DMBQ (ii) through the actions of fungal peroxidases, host peroxidases, or mild abrasion (Caldwell and Steelink, 1969;Keyes et al, 2007). (B) DMBQ (ii) and peonidin (iii) enter the parasite cells, possibly by nonselective diffusion (Shann and Blum, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Rapid ROS accumulation catalyzed by QR1 may also be associated with the growth of long densely positioned haustoria hairs. Arguing against the involvement of ROS in the direct modification of the haustorial cells is the observation that Striga radicals treated with DMBQ had reduced levels of ROS (Keyes et al, 2007). This suggests that ROS levels are controlled during haustorium development, at least in Striga, to a greater degree than might be predicted if they were directly used as developmental catalysts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent elucidation of a new role for reactive oxygen species (ROS)-molecules traditionally associated with defense-in host selection by parasitic angiosperms underscores the complex interplay between signaling events, and may open new strategies for intervention. 5 This new process, known as semagenesis for signal generation, was discovered in the parasitic Scrophulariaceae Striga asiatica. Previous results had suggested that the accumulation of the p-benzoquinone xenognosins, which regulate the transition between vegetative growth and development of the host attachment organ known as the haustorium, were dependant on parasite-derived H 2 O 2 .…”
Section: "Tell Me What You Eat and I Will Tell You Who You Are"mentioning
confidence: 99%
“…[1][2][3][4] In the recent study, fluorescence and transmission electron microscopies successfully defines both the cellular site of oxidant production as well as the sensitive feedback regulation by the xenognosin. 5 Indeed, ROS production by the parasite appeared insufficient to cross-link cell wall components or activate apoptosis in either plant, but was sufficient to generate the necessary p-benzoquinone xenognosins from host cell walls. Such precise control over ROS accumulation helps explain both the earlier reports of xenognosin signal integration by the parasite, 6 as well as how complications associated with using ROS as a secondary messenger in defense responses can be avoided during pathogen attack.…”
Section: "Tell Me What You Eat and I Will Tell You Who You Are"mentioning
confidence: 99%